Temporal partitioning by felids, dholes and their potential prey in northern Laos - Rasphone, A; Kalmer, JF; Macdonald, DW (Springer, 2020)
Temporal partitioning can allow sympatric carnivores to coexist, especially if overlap of other resources is high. Using camera trap data from 2013 to 2017, we investigated the temporal partitioning of a community of wild felids and a canid in Nam Et–Phou Louey National Protected Area, Laos, to determine the extent to which temporal avoidance might be facilitating coexistence of similarly sized carnivores. We also investigated temporal overlap of these carnivore species and their presumed main prey, to determine if their activity is likely most influenced by their prey or potential competitors. The dhole (Cuon alpinus) and clouded leopard (Neofelis nebulosa), the two largest carnivores, had low temporal overlap, and activity appeared to be synchronized with the main prey for dhole, but not clouded leopard. Thus, it was possible that clouded leopard used temporal partitioning to coexist with dhole. The temporal overlap of Asian golden cat (Catopuma temminckii) was high with clouded leopard and moderate with dhole, and overall appeared to be influenced most by its presumed prey species, rather than by its potential competitors. The two small felids had the least temporal overlap between any species, as the marbled cat (Pardofelis marmorata) was primarily diurnal whereas the leopard cat (Prionailurus bengalensis) was primarily nocturnal. Given that the two small felids reportedly have similar diets consisting of small rodents and birds, their temporal partitioning is likely to help facilitate their coexistence. For carnivore species in northern Laos that are most similar in body size and diet, temporal partitioning is likely to be an important mechanism of coexistence. Otherwise, temporal patterns appear to be synchronized with their main prey.